2015
DOI: 10.1016/j.canlet.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis by selective estrogen receptor modulators through blockade of cholesterol trafficking rather than estrogen receptor antagonism

Abstract: Selective estrogen receptor modulators (SERM) including tamoxifen are known to inhibit angiogenesis. However, the underlying mechanism, which is independent of their action on the estrogen receptor (ER), has remained largely unknown. In the present study, we found that tamoxifen and other SERM inhibited cholesterol trafficking in endothelial cells, causing a hyper-accumulation of cholesterol in late endosomes/lysosomes. Inhibition of cholesterol trafficking by tamoxifen was accompanied by abnormal subcellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The cholesterol depletion influences membrane-bound, major angiogenic signaling proteins, such as mTOR and VEGFR2, inhibits angiogenic signaling in endothelial cells, and suppresses angiogenesis (Figure 3). Replenishing the endothelial cells with cholesterol rescued the inhibitory effect of the cholesterol trafficking inhibitors on mTOR, VEGFR2, and angiogenesis [37,49,56,57]. This observation not only validates the essentiality of the membrane’s cholesterol level in angiogenic signaling, but also proposes a hypothesis that cholesterol trafficking inhibitors may be less effective in hypercholesterolemic individuals when used for anticancer applications.…”
Section: Summary and Future Perspectivesmentioning
confidence: 72%
See 2 more Smart Citations
“…The cholesterol depletion influences membrane-bound, major angiogenic signaling proteins, such as mTOR and VEGFR2, inhibits angiogenic signaling in endothelial cells, and suppresses angiogenesis (Figure 3). Replenishing the endothelial cells with cholesterol rescued the inhibitory effect of the cholesterol trafficking inhibitors on mTOR, VEGFR2, and angiogenesis [37,49,56,57]. This observation not only validates the essentiality of the membrane’s cholesterol level in angiogenic signaling, but also proposes a hypothesis that cholesterol trafficking inhibitors may be less effective in hypercholesterolemic individuals when used for anticancer applications.…”
Section: Summary and Future Perspectivesmentioning
confidence: 72%
“…However, the molecular mechanism that allows SERM to inhibit angiogenesis has not been explained until recently. Our group recently found that SERM, including tamoxifen, toremifene, clomifene, and raloxifene, inhibited cholesterol trafficking in endothelial cells [49]. Treatment of HUVEC with SERM strongly induced the NPC-like phenotype in the cells and blocked VEGFR2 and mTOR signaling.…”
Section: Cholesterol Trafficking Inhibitors As Anti-angiogenic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies have showed that some of the CADs (including the SERMs) have some incidental biological activities, i.e., drug-induced phospholipidosis (DIP)1718192021, cholesterol accumulation22, steatohepatitis23242526, and functional inhibition of acid sphingomyelinase (ASM) and acid ceramidase (AC)2728. Much of the incidental biological activities of the CADs are related to their structural properties; several CADs are weak bases which are protonated after entering the low pH of the endolysosome.…”
mentioning
confidence: 99%
“…Altogether a better understanding of cholesterol processes in ER+ BC is being unravelled in light of failed clinical response to selective ER modulators (SERMs) like Tamoxifen and aromatase inhibitors. Recently Shim et al found that endothelial and BC cell proliferation was inhibited in a cholesterol-dependent manner, unrelated to ER inhibition, by high concentrations of Tamoxifen [39]. Notably continued activation of ER signalling despite aromatase therapy or tamoxifen treatment has been attributed to non-aromatized molecules like 27 hydroxycholesterol (27HC) and 25 hydroxycholesterol (25HC).…”
Section: Discussionmentioning
confidence: 99%